Answer:
The zeros of given expression
is -1,
and
![-1-i√(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/92xyfasgjwkfbwzj1xs54l3maj45bbvib8.png)
Explanation:
Given expresssion is
![-x^3-3x^2=6x+4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/aeoy4oqs5wm3q28y3ddbc2qf4xgc8mje2n.png)
To find zeros of given expression we have to equate the expression to zero.
ie.,
![-x^3-3^2-6x-4=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dnrea6edatwpz1w49jmxanuq0wx03gtjit.png)
![-(x^3+3x^2+6x+4)=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4d1uwh774s9tdg4pp8emenxnanc3n9tb77.png)
![x^3+3x^2+6x+4=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/coajocasxmo0yvst8mfc6frdpgeqmr3a3d.png)
By using synthetic division
-1 | 1 3 6 4
| 0 -1 -2 -4
|________________
1 2 4 0
Therefore (x+1) is a zero
Now the quadratic equation is
![x^2+2x+4=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/gw5cngaohzxumdayukibl2qe8otv0tqwp3.png)
For quadratic equation
we have
![x=(-b\pm √(b^2-4ac))/(2a)](https://img.qammunity.org/2020/formulas/mathematics/high-school/ab45cdhbeliwcal3naam0rctuj1s2ka8cv.png)
Here a=1 ,b=2 and c=4 now substitute the values
![x=(-2\pm √(2^2-4(1)(4)))/(2(1))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/pzpw3j81ogsups6rsgs4vtxd17e30fn7lm.png)
![x=(-2\pm √(4-16))/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6jt9wtlmpmaon44pwzl8c1ysabexyg5lde.png)
![x=(-2\pm √(-12))/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ke5qey243zgswy5w03nj6sxr403ngiu8n5.png)
where
![i^2=-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gi5nlj0p4ye4meciplcgthfh9q4t15uxa5.png)
![x=(-2\pm i √(4* 3))/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ny57qvatafea0q8vpjnfgq00w7mxzdirnr.png)
![x=(-2\pm i √(4)√(3))/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ylgqhk6pitlnb2l60rmk8ho757qggqd9w8.png)
![x=(-2\pm 2i√(3))/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/f9cfmq3p4b689azrmq3onysn49jaz2pvew.png)
![x=2*((-1\pm i√(3)))/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5pxu4y475ivaww8wd8z0nn5x6bgob8ny4b.png)
![x=-1\pm i√(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nqarxo46lc0el7iv46iqws3qfkthx50imd.png)
Therefore
and
![x=-1-i√(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/g3docg4kiz94tk9e3o2ukdif0m22wfydvc.png)
Therefore the zeros are -1,
and
![-1-i√(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/92xyfasgjwkfbwzj1xs54l3maj45bbvib8.png)